Etiotropic therapy and chemoprophylaxis of influenza with neuraminidase inhibitors - T. G. Zubkova; I. I. Tokin; E. Yu. Karnaukhova; D. A. Lioznov (Медицинский совет, 2020)
Influenza is a common respiratory infection caused by viruses of types A, B and C. Characteristic of influenza infection is the development of intoxication and damage to the epithelium of the mucous membrane of the upper respiratory tract, often the trachea. Complications of influenza occur in 10–15% of patients. Most often it is pneumonia, bacterial focal infections (sinusitis, otitis, urinary and biliary tract infections), activation of chronic infections (tuberculosis, rheumatism). In influenza infection, as in the treatment of any infectious disease, the greatest importance belongs to etiotropic therapy. The world health organization recommends the use of neuraminidase inhibitors for etiotropic treatment of influenza. Currently, 2 neuraminidase inhibitors are used in the Russian Federation - oseltamivir and zanamivir. Both of these drugs are included in the clinical guidelines approved by the Ministry of health of Russia. In the Russian pharmaceutical market, oseltamivir is represented including the domestic drug Nomides in several dosages of 75 mg, 45 mg, 30 mg, which allows it to be used in children from 3 years. Etiotropic drugs should be prescribed as early as possible from the moment of clinical manifestation of the disease, optimally - in the first 48 hours from the onset of the disease, without waiting for laboratory verification of the diagnosis. The advantages of etiotropic therapy are reducing the risk of complications, shortening the period of fever and other symptoms. It is equally important to reduce the incidence of secondary complications requiring antibiotics and hospitalizations due to influenza. Etiotropic drugs for influenza therapy, including nomides, are used to prevent influenza infection. It should be noted that chemoprophylaxis does not replace vaccination against influenza, but is an auxiliary method of preventing the disease.